Sanitation access in the developing country: The impact of human development, income inequality, and economic growth - Sapta Suhardono; Iva Yenis Septiariva; Wisnu Prayogo; I Wayan Koko Suryawan (Regional Development Information Center, Universitas Sebelas Maret, 2024)
This study aimed to analyze the correlation between human development, income inequality, economic growth, and access to sanitation in Bali, Indonesia. The research used secondary data from the Indonesian Central Bureau of Statistics (BPS) on sanitation access, the Human Development Index (HDI), the Gini Ratio, and Gross Domestic Product (GDP) in Bali Province from 2017 to 2021. Multiple linear regression analysis was conducted to examine the relationship between these variables. The findings of the study showed that HDI has a significant positive correlation with access to sanitation in Bali, while GDP and Gini Ratio have no significant correlations. The results suggested that investing in human development is crucial for improving access to sanitation. Additionally, the study highlighted the importance of addressing income inequality and promoting sustainable economic growth in order to improve sanitation access. These findings will be important input to policy development for improving sanitation access in Bali Province and other developing regions.